2020
DOI: 10.1055/s-0040-1712124
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Preeclampsia in the First Trimester and Aspirin Prophylaxis: Our First Year

Abstract: Objective Preeclampsia is a major cause of perinatal and maternal morbidity and mortality. Our objective is to assess the performance of a combined screening test for preeclampsia in the first trimester and the prophylactic use of low-dose aspirin. Methods Prospective study of all women attending our hospital for the first-trimester screening of aneuploidies, between March 2017 and February 2018 (n = 1,297). The exclusion criteria were multiple pregnancy and major fetal abnormalities. Preeclampsia sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 30 publications
1
18
0
4
Order By: Relevance
“…Rastreio de pré-eclâmpsia no primeiro trimestre e profilaxia com aspirina: O nosso primeiro ano (5) Portugal 2020…”
Section: Título País/ Ano Objetivo Tipo De Estudo Resultadosunclassified
See 2 more Smart Citations
“…Rastreio de pré-eclâmpsia no primeiro trimestre e profilaxia com aspirina: O nosso primeiro ano (5) Portugal 2020…”
Section: Título País/ Ano Objetivo Tipo De Estudo Resultadosunclassified
“…Também se associa a pré-eclâmpsia, mesmo com ausência de proteinúria, valores laboratoriais anormais, especificamente plaquetopenia e hepatocitose, além do surgimento de sinais ou sintomas de envolvimento de órgãos-alvo, por exemplo, comprometimento renal identificado como insuficiência aguda através da dosagem de eletrólitos. (5,8) A pré-eclâmpsia está associada a maior chance de parto prematuro, baixo peso ao nascer e morte fetal. É importante realizar o tratamento e cuidados para diminuição dos riscos e agravamentos, durante as consultas clinicas deve-se identificar as mulheres que precisarão de uma vigilância mais cuidadosa, aumentando o número de consultas pré--natais de 4 em 4 semanas até 27 semanas, a cada 2 semanas entre 28 e 35 semanas e semanalmente a partir de 36 semanas.…”
Section: Relato De Experiênciaunclassified
See 1 more Smart Citation
“…Physician compliance of 96 to 99% has meanwhile been demonstrated with implementation of the FMF algorithm. 9,11 Although we didn't assess patient compliance in this study, it's clear that physician compliance with prescribing aspirin does not equate with patient compliance. In an observational cohort study, 44% of women identified as high-risk using maternal characteristics alone, were not compliant with the use of aspirin.…”
Section: Discussionmentioning
confidence: 98%
“…The prognosis correlates directly with this classification since early onset PET is linked to more serious complications and poor maternal and neonatal outcomes (Lisonkova and Joseph, 2013). A study by (Lourenço et al, 2020) showed that the first trimester screening of PET, which combines maternal factors, obstetric and medical history, and biochemical and biophysical markers, is useful for predicting early onset PET in a routine care setting. Therefore, the first trimester combination test with maternal risk factors and biomarkers should be used as a one step procedure to screen all pregnant women for preterm PET during early pregnancy (Poon et al, 2019).…”
Section: Discussionmentioning
confidence: 99%